Ammritā Prītama - Kavātaḏa, Savarana (Siṅgha Bradaraj̱a, 2009)
Reminiscences about Amrita Pritam, 1919-2005, Panjabi litterateur, by her daughter
In Panjabi
Keywords: Amrita Pritam 1919-2005; Authors; Panjabi